THE EFFECTIVENESS OF IMPLEMENTATION OF THE KOLAKA REGIONAL REGULATION NUMBER 7 YEAR 2017 CONCERNING IMPLEMENTATION A DAY WITHOUT POLLUTION CAR FREE DAY - Yudi Agusman; La Ode Asrun; Arafat Arafat (UNIVERSITAS PAKUAN, 2022)
The purpose of this study is to determine the effectiveness of Regent Regulation Number 7 of 2017 concerning the Implementation of a Day Without Car Free Day Pollution by the Kolaka Regency Transportation Office. The methods used in this study were analyzed using qualitative descriptive techniques. The location in this study was the Kolaka District Transportation Office. Based on the results of the study, in terms of achieving the objectives of the program implementation, it can run well because, in the Car Free Day activities that take place, there is involvement from several related parties, namely the Tourism Office, the Environment Agency, in supervising and securing the location where the car-free day activities have not gone well. In terms of integration in the implementation of car-free day, comfort and cleanliness at the location of the activities are running effectively, because there are still people who throw garbage in any place at the activity location and are also still found by swordsmen who sell at the location of car-free day activities. In terms of adaptation, in the implementation of the zero pollution day program carried out around Mandra Beach by the entire implementation team, , previously all SKPD (Regional Apparatus Work Units) involved prepared the needs for the implementation of activities starting from the installation of banners or billboards and also prepared prohibition signs or signs they would use it at the location of car-free day activities.